(untitled) (Actualité en allergologie et en immunologie au Canada, 2023)
Many oral abstracts, posters and case reports were presented at the American Academy of Allergy Asthma & Immunology (AAAAI) Annual Meeting which was held in February 2023 in San Antonio, Texas. We have selected the following seven articles due to their relevance to Canadian allergy and immunology clinical practice and research.